PEMETAAN GAMIFIKASI PADA MATA KULIAH HIDROLOGI BERDASARKAN MOTIVASI BELAJAR MAHASISWA PENDIDIKAN TEKNIK BANGUNAN - Siti Nurliati Aldina; Arris Maulana (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to determine what gamification is suitable for use in hydrology courses based on the learning motivation of students of Building Engineering Education, Jakarta State University, which can be used as a reference in developing hydrology learning applications / LMS.This study uses the Octalysis Gamification Framework method as a reference for determining gamification elements and quantitative methods to collect student motivation data. The population in this study were students of the Jakarta State University Building Engineering Study Program for 2020 2021 who had attended a hydrological course, the samples used in this study amounted to 42 students.The results of this study indicate that students' motivation towards hydrology courses is dominant on the core drive CD-1 Epic Meaning and Calling which is related to motivation to succeed in group study missions, CD-2 Development and Accomplishment which is related to motivation for learning achievement, CD-3 Empowering Of Creativity and Feedback related to motivation for creativity empowerment and instant feedback from lecturers, and CD-8 Loss and Avoidance References related to motivation due to fear of missing opportunities. Thus, the appropriate gamification used in hydrology courses based on student learning motivation is Narrative, Elitism, Cap Switcher, Status Point, Fixed Action Reward, Leaderboard, Quest List, Real-Time Control, Dynamic Feedback, Blank Fills, Booster, Progress Loss, Evanescence Opportunity, Status Quo Sloth.